2018
DOI: 10.1021/acs.jctc.8b00777
|View full text |Cite
|
Sign up to set email alerts
|

Performance and Scope of Perturbative Corrections to Random-Phase Approximation Energies

Abstract: It has been suspected since the early days of the random-phase approximation (RPA) that corrections to RPA correlation energies result mostly from short-range correlation effects and are thus amenable to perturbation theory. Here we test this hypothesis by analyzing formal and numerical results for the most common beyond-RPA perturbative corrections, including the bare second-order exchange (SOX), secondorder screened exchange (SOSEX), and approximate exchange kernel (AXK) methods.Our analysis is facilitated b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
27
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 113 publications
(325 reference statements)
1
27
0
Order By: Relevance
“…Therefore, the RPA + SOSEX approximation yields more accurate cohesive energies compared to experiment than the RPA. We note that similar findings have been obtained using related corrections to the RPA, such as AXK (Chen et al, 2018).…”
Section: The Random-phase Approximation and Its Connection To CC Theorysupporting
confidence: 87%
“…Therefore, the RPA + SOSEX approximation yields more accurate cohesive energies compared to experiment than the RPA. We note that similar findings have been obtained using related corrections to the RPA, such as AXK (Chen et al, 2018).…”
Section: The Random-phase Approximation and Its Connection To CC Theorysupporting
confidence: 87%
“…186 Account for the resulting leading-order term, referred to as ''approximate exchange kernel'' (AXK), considerably improves RPA energies and has been found to provide a more balanced correction to RPA than the SOSEX approach, when treating main-group compounds. 190 5.1.3 ACFD/RPA in electronic structure codes. As a general remark, it has unanimously been found that EXX/cRPA calculations are more reliable when based on KS states obtained from GGA-DFT calculations rather than Hybrid density functionals.…”
Section: Random-phase Approximation Of the Acfd Formulamentioning
confidence: 99%
“…It consistently overestimates the magnitude of the (negative) correlation energy and tends to slightly underestimate cohesive energies and overestimate bond lengths as well as lattice constants. 1,6,[11][12][13][14][15][16][17][18] This is supposed to originate from contributions in the ring terms of the RPA that violate the Pauli exclusion principle, as outlined in more detail in Section 3. By the merit of Wick's theorem such exclusion principle violating (EPV) contributions are exactly canceled by contributions in other terms of the exact many-body perturbation expansion where the offending states are exchanged.…”
Section: Introductionmentioning
confidence: 99%
“…To correct for this deficiency a number of post-RPA approaches have been proposed and have been assessed for a range of systems. 11,16,21 In direct ring coupled cluster doubles (drCCD) theory, the total energy can be calculated by anti-symmetrizing the final Coulomb interaction when tracing over the drCCD amplitudes. This approach offers a more balanced approximation to total correlation energies and some other properties but does not always improve energy differences.…”
Section: Introductionmentioning
confidence: 99%